The Use of ultrafiltration for removing interferences in the lowry microassay of extractable proteins in natural rubber latex gloves - Mok K L; Lai P F; Yip E (Journal of Rubber Research, 2001)
This study evaluates the use of ultra filtration in removing micro-solutes that might interfere in the Lowry microassay. Reference proteins, gloves extracts and 1, 3-diphenylguanidine were subjected to ultrafiltration using a commercial concentratoe, ahich has a membrane filter of 3kD molecular weight cutoff. Separated fractions were analysed for their reactivity by the MS 1392: 1998 Lowry microassay. Purified reference proteins with molecular weights greater than 3kD, showed high retentate recovery, which verified the efficacy of seperation of the ultrafiltration unit. Micro-solutes were evidently present in both the non-interfering and interfering glove extracts. Irrespective of their original extactable protein (EP) values, the micro-solute content for the non-interfering glove extracts was relatively constant at 28;. This is in contrast witht he marked variation observed for the interfering glove extracts. The ultrafiltration process caused an irrecoverable loss of approximately 5;- 6;. The total recovery was comparable for both the non-interfering and interfering glove samples. This indicates that the micro-solutes and/or their interfering components were not detrimental to the filter membrane, causing no obvious degradation of membrane integrity. Some samples may however, necessitate higher number of wash cycles to completely remove the interference and obtain accurate EP values.
Keywords: Bovine serum albumin; Interference; Lowry microassay; Natural rubber gloves; Natural rubber latex; Proteins; RRIM 701; Ultrafiltration